Civil Society Vocabularies and Signaling Value: Cases From Colombia and Ecuador. Issue 2 (3rd April 2017) - Appe, Susan; Barragán, Daniel; Telch, Fabian
Abstract : The context for civil society organizations (CSOs) in developing regions—restrictive policies, heightened accusatory and delegitimizing discourse, and decreasing international funds—leads in practice to major concerns for organized civil society. To confront this, CSOs are responding with the objective of explaining the work of organized civil society and its value. This article examines the discourses and tools used by organized civil society to frame its value in society in Latin America through the country cases of Colombia and Ecuador. Specifically, we look at the discourses and tools produced by national and subnational civil society networks that serve the sector as a whole. The article identifies key vocabularies found in the academic literature and discussed within policy spheres about civil society—mapping and spatial strategies, sustainability, and resilience. The article concludes with both opportunities and challenges to the application of these discourses and tools and with suggestions for next steps for research.